The impact of home-country conditions and geographical diversification on the domestic productivity of telecom multinationals: A multi-country study - Symeou, Pavlos C.; Merchant, Hemant (My University, 2019)
Purpose: Previous work in international business largely disregards the interplay between home-country conditions and firms’ geographical diversification – implying that, regardless of indigenous conditions, firms can modify their domestic performance (which the authors measure in terms of change in firms’ domestic productivity) merely by diversifying into international markets. The authors contest this view and argue that diversification does not substitute for home-country conditions. Rather, it moderates the baseline impact of home-country conditions on indigenous firms’ domestic performance. The purpose of this study is to describe these mechanisms and empirically examine their implications for indigenous firms’ performance. Design/methodology/approach: The authors investigate the above model based on a 20-year longitudinal analysis of 600 observations involving telecommunication incumbents from 65 countries. They control for possible reverse causality between firms’ international diversification (and other firm-specific factors) and their domestic performance, and conduct several robustness checks. Findings: The authors find – as hypothesized – that international diversification moderates the baseline performance impact of different home-country attributes in different ways. Such diversification does not have a uniform moderating effect on home-country attributes. In other words, the baseline effects of home-country conditions are altered as indigenous firms become more internationalized. Originality/value: Theoretically, this work bridges the micro- and macro-level arguments that interweave strands from the competitive strategy and national competitive advantage literatures. By unpacking diversification’s role vis-à-vis the effect of upstream (home-country) conditions on firm performance, the authors attempt to shed light on the mechanisms that help (or hinder) indigenous firms’ performance. Empirically, this study helps to reconcile seemingly opposite views about whether and, if so, how much home-country conditions shape indigenous firms’ expansion after they have diversified internationally.
Keywords: Competitiveness; Telecommunications industry; Geographical diversification; Firm’s domestic productivity; Home-country conditions